Modal Sosial Dan Potensi Wisata Dalam Pengembangan Kompleks Pariwisata Pelabuhan Kota Probolinggo Berbasis Masyarakat - Supriyanto; Nurul Jannah Lailatul Fitria (IAIN Madura, 2022)
The development of community-based tourism has become a tourism concept in order to optimize benefits for local communities. The reason is that the community will manage and organize tourism development programs. So that researchers conduct research to find out and assess the readiness of local communities, government, and other parties in the Port Area of ​​Probolinggo City in sustainable community-based tourism development activities. This research was carried out by applying qualitative methods with observation, interviews, and documentation techniques in the tourism environment and the community, government, and various private parties. In addition, it is supported by literature studies related to port tourism in Probolinggo City. The analytical framework used to identify the tourism development of the Probolinggo City Port is the stages prepared by APEC. The results of the research explained that the local community at the Port of Probolinggo City was ready and had relevant capabilities in developing tourism with a community orientation that was supported by the conditions of social capital and tourism potential of the Probolinggo City Port. Reference to 9 steps in community-based tourism management, such as identifying the interests of local communities and the form of community capacity in preparing tourism activities; identification of skills and forms of community ability to prepare tourism activities with community orientation; the role of regional heads in leading and organizational elements in port tourism areas; preparation and development of existing communities or organizations; Analysis of implemented partnership expansion; analysis of viewpoints or integrated understanding that has been aligned with the tourism program; analysis of product design and concept; analysis of market demand and promotional activities; analysis of the series of application and supervision of tourist areas. The nine references have been applied in the Probolinggo City Port complex tourism, but some are not yet optimal. Because many programs have just been launched and new facilities are being built and provided.